PENDAMPINGAN BIMBINGAN KARIER BAGI ANAK KAMPUNG SOSIAL ARGOPURO UNTUK MECIPTAKAN KESADARAN KARIER - Rosyidi, Fajar; Dwi Saputri, Niken (Proceedings of Annual Conference on Community Engagement, 2023)
Career guidance assistance for Argopuro children aims to create career awareness. This aims to ensure that children in the Agropuro social village have high career awareness. The focus of service lies in assisting children with career guidance and career awareness for children from the Argopuro social village. The method used is CBPR (Community Based Participatory Research). CBPR is a mixed method approach to researching things that society and communities want to achieve and usually uses a qualitative data collection approach strategy. Findings from the career counseling program show that the program has strong empowerment value, helping people achieve their career potential and increasing their independence in career decision making.